Efeito de inseticidas utilizados na cultura do tomateiro na infectividade de nematoides entomopatogênicos Steinernema carpocapsae e Heterorhabditis amazonensis (Nematoda: Rhabditida) - Sabino, Paulo Henrique de Siqueira (2015)
The entomopathogenic nematodes (EPNs) are biological control agents of different insect pests and may vary as to their degree of success, depending on the different action forms, specificity, adaptability to new environments, and can also occur synergism with other entomopathogenic agents. EPNs can be used in joint application with pesticides since that the products do not cause deleterious effects to EPNs. Thus, the present study aimed to correlate the reserve lipids of infective juveniles (IJs), their metabolic activity and mutualistic bacteria with insecticides that keeps viable IJs, however, reduces their infectivity to larvae Galleria mellonella. Two species of EPNs, Heterorhabditis amazonensis JPM4 and Steinernema carpocapsae ALL, which have potential to control Tuta absoluta were used. Eight insecticides registered for the tomato crop were used. The compatibility of insecticides with EPNs was assessed by mortality and infectivity of IJs 48 hours after contact with the insecticide. Vertimec® e Klorpan® reduce the infectivity of IJs. Moreover, these products reduced the lipid content and altered the metabolic activity of the IJs, however not influence the mutualistic bacteria. The change in metabolic activity and lipid reserves are factors that influence the infectivity of IJs, however other studies should be conducted to examine what other factors affect the reduction of infectivity.